Pengaruh Kualitas Produk, Harga, Dan Electronic Word of mouth Terhadap Keputusan Pembelian Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang Pengguna Aplikasi Shopee - Farhan, Juned; Rachma, N.; Rahman, Fahrurrozi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract In the current era of globalization, the internet has become a very important necessity for everyone. One of them is the rapid development of digital technology in the current era of globalization, people's lifestyles are also changing. This will ultimately have an impact on the economic field. Almost all activities currently use an online system, one of which is online shopping. quantitative research method with an explanatory research approach. The object of this research is FEB students at the Islamic University of Malang with a sample size of 110 respondents. The sampling technique used purposive sampling. Based on the results of the research analysis that there is a simultaneous influence between the variables of product quality, price, electronic word of mouth on purchasing decisions.  Keywords: Product Quality, Price, Electronic Word of Mouth, Purchase Decision